Penerapan Media Jejaring Sosial Edmodo untuk Meningkatkan Hasil Belajar Fisika Dasar - Siwi Puji Astuti (SAP (Susunan Artikel Pendidikan), 2018)
The teacher-centered learning in universities has been no longer inadequate and must be changed to the student-centered learning. There have been lately many easily accessible social media such as Facebook, Twitter, line, Instagram, Edmodo, and others. Those media can be used for educational purposes. The social media to be used in this research is Edmodo. The research is carried out to know the positive effect of the application of Edmodo social media on the results of basic physics learning. The research is conducted on first-year students of the 2018/2019 academic year at Universitas Indraprasta PGRI. The researcher uses a quantitative research method and a classical experimental design. The data analysis technique used is the Independent sample t-test using the SPSS 18. The research hypothesis to be tested is there is a positive effect on the application of Edmodo social media on the results of basic physics learning. The calculation results of the research have a sig value of 0.00 <0.05, indicating that there is a positive effect of the application of Edmodo social media on the results of basic physics learning. In conclusion, the results of the research show that there is a positive effect of the application of Edmodo social media on the results of basic physics learning